Los siete hermanos chinos - Mahy, Margaret; Tseng, Jean.; Tseng, Mou-Sien. (New York : Scholastic Inc., 1994)
Seven Chinese brothers elude execution by virtue of their extraordinary individual qualities.
"Mariposa, Scholastic en espanol"--Cover.
Translation of: The seven Chinese brothers.
Keywords: Fairy tales; Folklore -- China; Spanish language materials